The Need to Teach Grammar in IELTS Listening Class - Rahmarni Sawitri; Riyanto Riyanto (Scope : Journal of English Language Teaching, 2022)
The aim of this research is to examine the effect of grammar mastery on listening skills. Does someone’s mastery of grammar affect his listening skills? If it does, to what extent? To answer these questions, data, in a form of test answers were collected from students taking the IELTS Preparatory Class. The Listening section in IELTS consists of several types of questions including gap completion, matching and multiple choice questions. The focus of this research is on the gap completion questions as these types of questions  require test takers to write down words/phrases/numbers as the answers; therefore, grammar mistakes are noticeable if there are any. Many students find the gap completion section quite challenging as they have to complete the blanks with a word or phrase used in a conversation accurately in terms of both spelling and grammar. Consequently, being able to get the right word or phrase to answer the question is important. The researchers tried to examine whether knowing some grammar can improve test takers’ possibility of getting correct answers. The finding show that students’ mastery of grammar, to some extent, has an effect on their listening skills. Knowing some grammar can help students get grammatically correct answers. As grammar is not a learning focus in most IELTS Preparatory classes, it is recommended that teachers select what grammar points should be addressed, to a certain degree, in order to improve test takers’ listening comprehension and accuracy.